Sustaining a community-managed library through volunteers: a case study of ULiang Library, Tronoh Mines New Village, Kampar - Chuah, Ee Xin; Chuah, Tian Yin; Lim, Kean Boon; Moo, Shiao Lim; Tay, Yi Jing (2020)
The sustainability of community engagement is a growing concern in society as the number of community engagement programs is increasing and community engagement is proven to be beneficial to the community. Community-managed library is one of the community engagement programs,that is vital to serve and to improve the community. Community- managed library is a library that fully depends on the funds from the community and it was mostly staffed by the volunteers. This type of library is in need of volunteers to support their daily operations as it does not have a lot of money to hire paid staff. Volunteers that are of different expertise help to enable them to develop the capacity in sustaining community- managed libraries. Yet, community-managed library is currently facing a shortage of volunteers. Besides, there is limited research about the reasons for lacking volunteers in operating community library. By bridging the gap, this research looks into a case study of U- Liang Library in Tronoh Mines, Kampar, one of the community-managed libraries in Malaysia, to find out the reasons for lacking volunteers. This research aims to study reasons that hinder volunteer's involvement at a community-managed library and to identify ways to sustain a community-managed library. This qualitative research employed in-depth interview as the research method whereas snowball sampling was applied to choose the interviewees for our research. This research generated two types of factors that motivate volunteerism which are personal factors and environmental factors and also the ways to increase volunteers. On a side note, this study also offered ten solutions for the community-managed libraries on how to sustain the library as the results from multiple journals indicated that currently the libraries are facing hardship in sustaining themselves. However there are a few limitations for this study and one of them is a single case study does not reflect entirely the complexity of problems that faced by the entire community-managed libraries across Malaysia or internationally. In addition, snowball sampling limited the diversification of interviewees for this research as most of them were either volunteers or committees of the library but lacking of the opinions from the library users. Throughout the study, there were recommendations generated for future study as well. To address the limitation of snowball sampling, it is recommended to opt for judgement sampling for future research about this topic as it allows the researcher to approach more diversified respondents, providing more objective results to represent the findings of a research. Moving on, it is also recommended to expand the investigation scope of community-managed library in future research by studying more community-managed libraries to provide a more comprehensive perspective, fruitful existing literature and the creation of new solutions in sustaining community-managed libraries. It is also suggested to refine the future study by incorporating the views of local children, as it would provide different findings from various perspectives. There are also four expected challenges suggested in this study for future research which are change of authorities, change of a vision of the authorities, the need for a community- managed library in a local community and finally elevated expectations of a local community. In a nutshell, the research conducted through in-depth interview with the local community that was related to U-Liang library had successfully identified the ways to sustain a community- managed library after knowing the reasons that hinder volunteer’s involvement at the community-managed library. The findings provided good evidence against the research objectives. It is possible to use this research to highlight the ways in attracting volunteers that other community-managed libraries could execute to sustain in the future.